A Plan For Improving The Quality Of West Java Private Education Lecturers By Shareing Tacit Knowledge - Zhang, Yang; Gomesª, Lorraine Rayelle (Yayasan Pendidikan Belajar Berdikari, 2023)
Objective research This test will include knowledge, relationships with values, and altruistic conduct. Study This was completed in a private college in West Java using a quantitative and qualitative approach. Quantitative approach sample lecturer up to 294 persons. Approach qualitative by using three sources to find person leaders in higher education. According to research findings, conduct altruism is the best predictor of desire. Perceived value support is a crucial component of information sharing between lecturers on both an internal and external level. conclusions from the data This calls for the routine discussion of study programs at the lowest structural level, as well as discussions at the faculty and university levels, as well as discussions with party external Good fellow academics or with non-academicians, before activity. Regulations that guarantee quality as a tool for control must be applied to this. All of these ideas are capable of improving lecturer caliber and bringing about the Tri Dharma of Higher Education.